34.1k views
3 votes
3x + 2y = 12

2x + 5y = 8
process of elimination? how do I get the answer for this kind of question?​

User Rjmcb
by
6.2k points

1 Answer

2 votes

Answer:

(4, 0)

Explanation:

To use elimination, you need to make the coefficients of one of the variables the same in each equation. For example, we can multiply the first equation by 2 and the second equation by 3:

6x + 4y = 24

6x + 15y = 24

Now we can subtract the equations, eliminating the x terms.

(6x + 15y) − (6x + 4y) = 24 − 24

11y = 0

y = 0

Now plug into either equation to find x.

3x + 2y = 12

3x + 0 = 12

x = 4

User Nikolaos
by
5.8k points